SOCIALIZATION OF THE UTILIZATION OF ORGANIC FRUIT AND VEGETABLE KITCHEN WASTE FOR PRODUCTION OF ECOENZYMES - Lestari, Trijati Puspita; Indriani, Dini; Ainiyah, Qurrotul; Putri, Dewi Arimbi Tri Jaya; Yuliana, Firda; Akbar, G. Najikhul (LPPM Universitas Flores, 2026)
Household waste management, especially organic waste from the kitchen, is one of the serious problems faced by rural communities in Indonesia. Waste in the form of fruit peels and vegetable scraps from daily cooking activities is often not managed properly so it has the potential to pollute the environment and cause health problems. The purpose of waste management activities through the production of ecoenzyme is to assist the community of Tenggiring Village, Sambeng Sub-district, Lamongan Regency, in processing kitchen waste, such as vegetables and fruits, into valuable products. This activity is crucial considering the increasing global warming and the growing volume of household waste, thus processing organic waste into eco-enzyme can be an environmentally friendly solution. The fermentation product of eco-enzyme has many benefits, such as a natural floor and toilet cleaner, unclogging drains, fertilizing plants, repelling insects, and its residue can be utilized as organic fertilizer. The method used was participatory through socialization, counselling, and direct demonstration with the involvement of Universitas Muhammadiyah Lamongan students. The results show that the residents were able to understand and practice eco-enzyme production using simple ingredients such as brown sugar, vegetable and fruit residues, water, and recycled containers with a fermentation process of three months. The community showed high enthusiasm since the product proved useful for household, environmental, and agricultural needs, while also reducing the volume of organic waste. This activity had a positive impact in increasing environmental awareness among the community and demonstrated that organic waste management can be implemented in an affordable, easy, and sustainable way.